Survey of nutritional practices during therapeutic hypothermia for hypoxic-ischaemic encephalopathy. Issue 1 (26th July 2017) - Hazeldine, Beth; Thyagarajan, Balamurugan; Grant, Michellee; Chakkarapani, Elavazhagan
Abstract : Objective: To evaluate current nutritional practices during and after therapeutic hypothermia (TH) for infants with hypoxic-ischaemic encephalopathy (HIE) in UK neonatal units. Study design: Email survey of neonatal clinicians. Setting: UK neonatal units providing active TH. Patients: Neonates cooled for HIE. Methods: Email survey including questions regarding the timing of starting enteral feeds, volumes, frequency and parenteral nutrition (PN) use and availability of guidelines. Results: Forty-nine responses were received (49/69, 71%). The rate of enteral feeding during TH and rewarming was 59% (29/49). There was a significant linear trend for the increase in the proportion of units starting enteral feeds (p=0.001) during TH. As compared with post-TH period, significantly lower milk volumes were started during TH (median (range): 7.5 mL/kg/day (1.5–24) vs 17.5 mL/kg/day (7.5–30), p=0.0004). During TH, breast milk was primarily used by 52% of units predominantly as 2–3 hourly feeds, and volumes were increased as tolerated in 55% of units. Only 29% (14/49) of units used PN, with 86% (12/14) of those offering enteral feeds during PN. Guidelines for feeding during TH were available in 31% (15/49) of units. Conclusions: Many neonatal clinicians offer enteral feeds predominantly using expressed breast milk, with or without PN, during TH, although with huge variability. The heterogeneity in the nutritional practice underscores the need for assessing the safety of both enteral and parenteral feeding during TH.